The Influence of Instagram Social Media and User-Generated Content on Purchase Decision Through Brand Trust at Alligator Roastery Medan - Dwi Sakinah; Endang Sulistya Rini; Yeni Absah (Journal of Business Management, 2026)
Indonesia ranks fourth globally in coffee production, yet faces challenges in domestic market penetration. This study examines how Instagram social media marketing and User-Generated Content (UGC) influence purchase decisions through brand trust at Alligator Roastery Medan, a specialty coffee business experiencing declining customer visits from 680 daily visitors in 2022 to 420 in 2024. Using quantitative methodology with PLS-SEM analysis on 161 respondents selected through purposive sampling, data were collected via structured questionnaires. Results indicate that Instagram positively influences brand trust (β=0.423, p=0.004) and purchase decisions (β=0.298, p=0.005). UGC significantly affects brand trust (β=0.428, p=0.004) but shows no significant direct effect on purchase decisions (β=0.194, p=0.097). Brand trust mediates both relationships significantly and demonstrates the strongest direct effect on purchase decisions (β=0.456, p=0.000), explaining 80.8% of variance in purchase decisions. Findings suggest that digital marketing strategies must prioritize building brand trust through consistent, authentic content and leveraging consumer-generated content to enhance credibility and drive purchase behavior in the specialty coffee market.